2014
DOI: 10.1007/s11769-014-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of industrial relocation on Chinese regional economic growth disparities: Based on system dynamics modeling

Abstract: The economic growth of China has led to increasing growth disparities between regions. Such disparities are uncontrolled and are severely negative symptoms in the process of economic development. On the basis of system dynamics (SD) modeling and the relationship between industrial relocation and regional economic growth, we construct a model of the interrelationship between the two aforementioned phenomena. The model is an effective and creative exploration for examining effects of industrial relocation on Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, some differences were noted between Chinese and overseas returnees; for instance, Chinese returnees were found to be more frequently in waged employment, whereas overseas returnees are more inclined to start their own business. This may be because more Chinese manufacturing industries are moving from developed urban areas to less developed areas (Wu, Li, Sun, & Liang, 2014). The concentration of manufacturing factories in cities and towns has prompted returnees to settle in cities and towns.…”
Section: Discussionmentioning
confidence: 99%
“…However, some differences were noted between Chinese and overseas returnees; for instance, Chinese returnees were found to be more frequently in waged employment, whereas overseas returnees are more inclined to start their own business. This may be because more Chinese manufacturing industries are moving from developed urban areas to less developed areas (Wu, Li, Sun, & Liang, 2014). The concentration of manufacturing factories in cities and towns has prompted returnees to settle in cities and towns.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding the influence of trade balance, Zhang et al [31] found that regional carbon spillover is mainly concentrated in the coastal provinces but it contributes to an increase of carbon emissions in the central and western regions, and the coastal and inland provinces contribute to the increase of national carbon emissions through interregional imports and exports. In addition, because of differences in the economic development, technological progress and diffusion effects among regions, industrial transfer has been occurring [32]. Xu et al [33] reveal that for every 1% increase in industrial transfer, there is a 0.327% increase in industrial carbon transfer before passing the turning point.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the effect of the alternative process of new energy to obtain power-wasting and non-clean energy was greater than the effect of GDP growth in achieving the carbon reduction target (Xu et al, 2006). However, these factors were dependent apparently on income level or on technical progress factors, which can lead to a significant autocorrelation effect (Wu et al, 2013). In addition, the models derived from these factors were commonly highly difficult to interpret.…”
Section: Factors Influencing Carbon Emissionmentioning
confidence: 99%